The Role of Social Capital in Promoting Administrative Health and Transparency in Iranian Governmental Organizations: A Case Study of the General Directorate of Education of Tehran City - Parsa, Majid; Modami, Hossein; Alaei Noor, Mehri (Management Strategies and Engineering Sciences, 2027)
The present study aimed to investigate the role of social capital in promoting administrative health and transparency, considering the mediating role of organizational health in the General Directorate of Education of Tehran City. In terms of purpose, this research was applied, and regarding the method of data collection, it was a descriptive-survey study of a correlational nature. The statistical population consisted of all employees and managers of the General Directorate in 2025, from whom 400 participants were selected through stratified random sampling. The research instrument was a standardized questionnaire comprising the dimensions of social capital (structural, relational, and cognitive), organizational health, administrative health, and transparency, whose validity and reliability were confirmed. Data were analyzed using Structural Equation Modeling (SEM) and SmartPLS software. The findings indicated that all research hypotheses were supported. Social capital had a strong and positive effect on organizational health (β = 0.65). Furthermore, organizational health exerted a significant direct effect on administrative health (β = 0.58) and transparency (β = 0.52). The results of the mediation analysis using the bootstrap method revealed that organizational health functioned as a full mediating variable, such that a substantial portion of the effect of social capital on administrative health (indirect effect = 0.38) and transparency (indirect effect = 0.34) was transmitted through this pathway. The direct effects of social capital on these two variables were weaker but remained statistically significant. Among the dimensions of social capital, the relational dimension (trust and norms) emerged as the strongest predictor of organizational health. Therefore, it can be argued that a fundamental strategy for enhancing administrative health and transparency in governmental organizations is the deliberate strengthening of social capital, particularly through trust-building and the development of collaborative networks. By improving overall organizational health, such investment provides the necessary foundation for the spontaneous and sustainable emergence of healthy and transparent administrative behaviors. The findings of this study underscore the necessity of shifting from purely control-oriented approaches toward a paradigm of capacity-building and internal trust in Iran’s public administration.